You Take Care of the Drive, I Take Care of the Rule: A Traffic-Rule Awareness System Using Vehicular Sensors and Mobile Phones - Xing Zhang; Jidong Zhao; Jinchuan Tang; Bang Liu (International Journal of Distributed Sensor Networks)
Traffic rules are used to regulate drivers' behaviours in modern traffic systems. In fact, all driving behaviours are presented by vehicles' behaviours. If vehicles have awareness of their behaviours, it is possible that traffic rules are able to regulate vehicles instead of drivers. There are three advantages of vehicle regulation: (1) without worrying about violations of traffic rules and searching for traffic signs, drivers can pay more attention on emergency situations, such as jaywalking. (2) Many traffic violations are due to attention distraction; machines do not have the attention issues; therefore they can provide good traffic-rule obeying. (3) New traffic rules can be spread and applied more quickly and effectively through the Internet or Vehicular Ad hoc NETworks (VANETs). In this paper, we propose a novel traffic-rule awareness system using vehicular sensors and mobile phones. It translates traffic rules into combinations of vehicular sensors, GPS device, and Geography Information System (GIS); the system can tell whether a driver violates the traffic rules and help him to amend his driving behaviour immediately. Experiments in real driving environments show that our system can be aware of the traffic rules accurately and immediately.